Analysis of Students' Intuitive Thinking Abilities in Solving Mathematical Problems on Integer Topics - Noera Shikin; Nizlel Huda; Ade Kumalasari (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study aims to analyze and describe students' intuitive thinking abilities in solving mathematical problems on the topic of integers. This research employs a qualitative descriptive method. One research subject (S1) will be selected using purposive sampling based on their ability to demonstrate initial indications of intuitive thinking, such as the accuracy and speed of their initial response to a problem. The research instrument consists of one integer problem-solving test question designed to assess intuitive thinking abilities. Data is collected through triangulation using the think-aloud technique during the problem-solving process, followed by a semi-structured interview to explore the subject's (S1) reasoning and intuitive thought processes. Data is analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results reveal that intuition, specifically the common-sense type, acts as a cognitive bridge that accelerates the emergence of ideas and the formulation of problem-solving strategies. This intuitive thinking characteristic is demonstrated through the application of systematic strategies, logical reasoning, and a strong reliance on prior learning experiences. These findings indicate that learning experiences can serve as a crucial foundation in forming effective mathematical intuition. Therefore, mathematics instruction should be designed to enrich student experiences through a variety of problem-solving tasks to develop students' intuitive thinking abilitie